(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2013)
Textural characteristics of silica obtained from the gels have been introduced, which were formed in a pulsing magnetic field. It is shown, that all the characteristics of the resulting silica porosity, especially the pore distribution according to the size, essentially depend on the frequency of the magnetic field. It has been suggested that in dilute gels of the polysilitic acids pseudo-mesophase aggregate systems may be formed, which similar to liquid crystaline structures are capable of restructuring under the influence of weak electromagnetic fields.